Audio-Visual Media Learning in Arabic Language Acquistion - Firdaus, Ananda Zalfa; Hidayah, Vina (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Audio visual media provides extensive interaction activities between students and learning materials that are easy to access anytime and anywhere. This is in accordance with interaction theory in second language acquisition which emphasizes the importance of response and active participation in learning activities. Through audio-visual media, students will more easily grasp the meaning of the material presented so that students are able to express it through spoken language. The aim of the research is to determine the suitability of using audio-visual media in second language acquisition for Arabic language students. The research uses the library research method, a data collection technique by reviewing books and articles related to the research topic. The results of library research on the use of audio-visual media in acquiring Arabic, students are more enthusiastic in learning Arabic, the process of learning Arabic is fun, students easily understand the material through audio-visual media with quality determination criteria. Several psychologists explain that the connection between second language acquisition and second language learning can improve memory and increase motivation in using audio-visual media.